2004
DOI: 10.1002/cpp.405
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behaviour therapy for good and poor prognosis generalized anxiety disorder: a clinical effectiveness study

Abstract: Cognitive behaviour therapy (CBT) for generalized anxiety disorder produces variable results. It would be valuable to identify which patients respond well to brief CBT and whether increased intensity of therapy improves outcome for those with a poor prognosis. This clinical effectiveness study was designed to address these issues using a prognostic index developed from earlier research. Suitable patients were given five sessions of CBT if they had a good prognosis and either 9 or 15 sessions of CBT if they had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 39 publications
(29 reference statements)
6
26
2
Order By: Relevance
“…However, trait-anxiety levels were similar to the levels reported by Ost and Breitholtz (2000) and Arntz (2003) in their applied relaxation treatment conditions, and by Borkovec and Costello (1993) in CBT. Furthermore, pretreatment worry scores assessed by the AnTI in the present study were similar to those reported by Durham et al (2004) in their treatment study. Thus, the current sample appears to consist of patients comparable with patients treated in other trials.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…However, trait-anxiety levels were similar to the levels reported by Ost and Breitholtz (2000) and Arntz (2003) in their applied relaxation treatment conditions, and by Borkovec and Costello (1993) in CBT. Furthermore, pretreatment worry scores assessed by the AnTI in the present study were similar to those reported by Durham et al (2004) in their treatment study. Thus, the current sample appears to consist of patients comparable with patients treated in other trials.…”
Section: Resultssupporting
confidence: 83%
“…Recent attempts to improve treatment have combined these treatment elements, and increased the amount of therapy delivered (e.g. Borkovec, Newman, Pincus, & Lytle, 2002;Durham et al, 2004). However, so far treatment outcomes have not improved.…”
Section: Introductionmentioning
confidence: 97%
“…In Trial 7, those patients (identified as having good prognosis) who were allocated to brief CBT had the most favourable outcome, whereas there was no significant difference between the standard CBT and intense CBT groups. 116 It was concluded from this study that patient characteristics are a more powerful influence on outcome than the length of therapy. Finally, in Trial 8, 12 sessions of therapistdelivered CBT were found to be more effective than six sessions of CBT, but not more effective than computer-augmented CBT over six sessions at post-treatment.…”
Section: Introductionmentioning
confidence: 98%
“…117 A full description of the trial method can be found in the original report. 116 In the original trial poor prognosis patients receiving intensive CBT did not fare any better than those receiving standard CBT, whereas the good prognosis patients fared best overall, despite receiving only brief therapy. 118 which incorporated the cognitive and behavioural theories of panic 118,119 and standard cognitive and behavioural techniques.…”
mentioning
confidence: 99%
“…Borkovec et al, 2002;Yonkers et al, 2000). The CASP index was used in a clinical effectiveness study to test whether or not more intensive CBT (15 versus nine sessions) was more effective with poor prognosis GAD patients (Durham et al, 2004). A comparison group of good prognosis GAD patients (low scores on the CASP) was given brief CBT (five sessions).…”
Section: The Search For Moderating Variablesmentioning
confidence: 99%